Firm Performance and the Nature of Agency Problems in Insiders-controlled Firms: Evidence from Pakistan (The Pakistan Development Review, 2012)
More than two centuries ago, Adam Smith (1776) showed skepticism about the efficiency of joint stock companies because of the separation of management from ownership. He observed that managers of joint stock companies cannot be expected to watch over the business with the same anxious vigilance as owners in a partnership would. Adam Smith’s worry remained buried for a century and a half until Berle and Means (1932) rekindled interest in this area when they hypothesised in their book that dispersed shareholding is an inefficient form of ownership structure. They argued that separation of ownership and management control has changed the role of owner from being active to the passive agent. Dispersed shareholders lack incentives to monitor self-interested managers who possess only a small fraction of the total shareholdings. The propositions by Adam Smith (1776) and Berle and Means (1932) received some support when Jensen and Meckling (1976) tied together the elements of property rights, agency costs, and finance to develop a theory of ownership structure of a firm. Jensen and Meckling asserted that agency costs are real, which the owner can reduce either by increasing ownership stake of the agent in the firm or by incurring monitoring and bonding costs. In early tests, several research studies supported the views of Jensen and Meckling. However, these studies did not account for endogeneity problem.